2021
DOI: 10.1186/s12891-021-04053-7
|View full text |Cite
|
Sign up to set email alerts
|

Dedifferentiated chondrsarcoma: a clinicopathologic analysis of 25 cases

Abstract: Background To investigate the clinical, imaging and pathological features of dedifferentiated chondrosarcoma for better diagnosis. Methods Patients who had been confirmed to have dedifferentiated chondrosarcoma were enrolled in this study and analyzed in the clinical, imaging and pathological data. Results Twenty-five patients had pathologically confirmed dedifferentiated chondrosarcoma including 15 ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Dedifferentiated chondrosarcoma is a rare highly aggressive tumor which manifests in 6 t h to 7 t h decade of life with no gender predilection. [1][2][3] However, when the chondrosarcoma is secondary to an enchondroma, the presentation is earlier, as seen in this case. 9 Pain, swelling, increase in size of an enchondroma or a recurrence after excision should alert the clinician to look out for a malignant transformation.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…Dedifferentiated chondrosarcoma is a rare highly aggressive tumor which manifests in 6 t h to 7 t h decade of life with no gender predilection. [1][2][3] However, when the chondrosarcoma is secondary to an enchondroma, the presentation is earlier, as seen in this case. 9 Pain, swelling, increase in size of an enchondroma or a recurrence after excision should alert the clinician to look out for a malignant transformation.…”
Section: Discussionmentioning
confidence: 53%
“…Other components which can be seen are malignant fibrous histiocytoma, leiomyosarcoma, angiosarcoma, rhabdomyosarcoma, lipoblastoma and very rarely an epithelioid sarcoma. 1,9 The common sites involved by DDCS are femur and pelvis while humerus, ribs, spine tibia and upper extremities are rarer sites. 4 In a dedifferentiated chondrosarcoma, the cartilaginous component is usually seen within the bone and the dedifferentiated component exists outside in the soft tissue.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Liu et al 32 reported the prognosis in 23 patients with DDCS. Cao et al 39 investigated the clinical, imaging, and pathological features in 25 cases of DDCS. Gong et al 40 analyzed the clinical, histopathological, and immunohistochemical features of 57 cases of DDCS.…”
Section: Discussionmentioning
confidence: 99%